2021
DOI: 10.1002/eco.2321
|View full text |Cite
|
Sign up to set email alerts
|

Green roof vegetation management alters potential for water quality and temperature mitigation

Abstract: The global increase of urban impervious land cover poses a significant threat to the integrity of river ecosystems. Hence, it is critical to assess the efficiency of green roofs (GR) to mitigate the negative impacts of urbanization on river ecosystems, such as thermal surges and pollutants. In this study, we evaluated the ecohydrological behaviour of two fully established GR under differing management regimes at the Chicago Botanical Gardens from July to September 2019. The drainage outflow from a non‐vegetate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 69 publications
0
13
0
Order By: Relevance
“…Soil moisture is normally measured using sensors that detect the volumetric water content of the surrounding soil. Soil moisture sensors are frequently used in green roofs, [19][20] rain gardens, 21 and natural areas. 22 Volumetric water content data can be used to estimate the total stormwater storage provided by NBS, determine the impact of antecedent soil moisture on the response to rain events, and monitor in situ conditions for plant growth.…”
Section: Instrumentation Strategies For Nature-based Solutions Key Mo...mentioning
confidence: 99%
See 1 more Smart Citation
“…Soil moisture is normally measured using sensors that detect the volumetric water content of the surrounding soil. Soil moisture sensors are frequently used in green roofs, [19][20] rain gardens, 21 and natural areas. 22 Volumetric water content data can be used to estimate the total stormwater storage provided by NBS, determine the impact of antecedent soil moisture on the response to rain events, and monitor in situ conditions for plant growth.…”
Section: Instrumentation Strategies For Nature-based Solutions Key Mo...mentioning
confidence: 99%
“…In engineered NBS designed with a discharge or overflow pipe, outflow is frequently measured using a flow meter 19,20,30 or a weir and pressure-transducer water level sensor. 28 In addition to outflow from the NBS systems, discharge is often measured within the stormwater drainage system that receives water from the NBS to determine performance in terms of the reduction of stormwater flow.…”
Section: Instrumentation Strategies For Nature-based Solutions Key Mo...mentioning
confidence: 99%
“…Indeed, the Autobot-WQ were drawing water from roof drainage pipes, where the space was highly restricted, and the flow depths were small at the beginning and end of runoff, and where conventional autosamplers would not have worked for this application due to these constraints. Ouellet et al (2021) provide the full detail of the green roof experiment realized in 2019, and here, we used unpublished results for the same study design. The study was conducted on two semi-intensive GR, adjacent to a non-vegetated roof from July to September 2019 and located at The Daniel F. and Ada L. Rice Plant Conservation Science Center at the Chicago Botanic Garden, Illinois, United States (42.14 °N, −87.78 °E).…”
Section: Case Study 2: Green Roof Efficiency To Mitigate Water Qualit...mentioning
confidence: 99%
“…River pollution is a remarkably complex issue with multiple sources contributing across variable time scales, meaning that a high spatial density of sampling is required to facilitate understanding. Urban areas typically display a higher number of pollution sources and can have strong negative water quality impacts (Walsh et al, 2005;Booth et al, 2016;Ouellet et al, 2021). Urbanization is typically associated with increased pressure on urban streams as physical habitats are modified (e.g., channelization) and water quality impaired (e.g., by road runoff and effluent inputs) (Walsh et al, 2005;Palmer et al, 2010;Booth et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In the two VRs observed by Thuring and Dunnett (2019), less than half the original planted species persisted over time, but the entirety of the green cover was maintained by colonizing species. (Ouellet et al, 2021) compared managed and unmanaged VR and observed that the unmanaged had a greater capacity in reducing thermal surges associated with storm events. Not only that, but Schrieke and Farrell (2021) demonstrated spontaneous VRs can reduce construction costs, applying less pressure on property value.…”
Section: Introductionmentioning
confidence: 99%